2021
DOI: 10.1021/acs.jpcc.1c06227
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Cu(II) MOFs Formed via Microemulsion: Vibrational Mode Characterization Performed using a Combined FTIR, Synchrotron Far-IR, and Periodic DFT Approach

Abstract: Two Cu­(II) metal–organic frameworks (MOFs) were prepared on the nanoscale at room temperature using a microemulsion method, namely, [Cu3(BTC)2(H2O)3] (BTC = benzene-1,3,5-tricarboxylate), known as HKUST-1 (1), and [Cu2(OH)­(BTC)­(H2O)]·2H2O (2). Thermochemical and gas sorption properties of the microporous topologies were characterized by mid- and far-infrared vibrational spectroscopy, supported by periodic density functional theory calculations. The mid-infrared profile of 1 appeared altered in response to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…S4†) of the COOH group in the free ligand H 4 L indicates the successful coordination of the organic ligands H 4 L with the Cu( ii ) centres. 37 Similarly, the PXRD of H-2 is consistent with the simulation, indicating the synthesis of highly crystalline H-2 . H-1 , H-2 , and H-1e have been successfully synthesized under the conditions of solvothermal and electrochemical synthesis (Fig.…”
Section: Resultssupporting
confidence: 74%
“…S4†) of the COOH group in the free ligand H 4 L indicates the successful coordination of the organic ligands H 4 L with the Cu( ii ) centres. 37 Similarly, the PXRD of H-2 is consistent with the simulation, indicating the synthesis of highly crystalline H-2 . H-1 , H-2 , and H-1e have been successfully synthesized under the conditions of solvothermal and electrochemical synthesis (Fig.…”
Section: Resultssupporting
confidence: 74%
“…The observed rigidity of the T d subunits therefore constrains the vibrational degrees-of-freedom of the system, which results in the distinctive far-IR profiles for each framework where peaks associated with T d hindered rotational and deformation are populated. In addition, previous studies 36 have shown that, beyond acting as a diagnostic between HOF structures, the far-IR region is also highly sensitive to the changes in the (i) physical environment (temperature and pressure), (ii) morphology and pore/channel architecture, and (iii) solvent environment for prototype MOF systems. Similar experiments would be of high relevance to the HOF materials featured in this study, with particular focus toward the characterisation of water-of-hydration network within the channels through variable temperature and solvent substitution studies.…”
Section: Discussionmentioning
confidence: 99%
“…In coordination polymers and molecular crystals, these low frequency vibrational modes have been shown to be highly sensitive to the morphology of the network. 36,52,53 For example, it is observed that band profiles are altered with (i) change of phase, (ii) change of temperature and pressure conditions, and (iii) through the effect of retained solvent -in this case waterwhich can all act to perturb the equilibrium frequency of a given vibrational mode.…”
Section: Ctaáctc (2)mentioning
confidence: 99%
See 2 more Smart Citations